CORPORATE RELATIONS IN RUSSIAN UNIVERSITIES: BREAKING TRADITION - Valentin P. Babintsev (Высшее образование в России)
The article addresses the problem of corporate relation evolution in modern Russian Universities in the context of higher education system reforming. The corporate relations are characterized as a system of informal interrelations and interactions of colleagues where a personal factor plays the main role. It is noted that their development was traditionally defined by stability of organizational structure of Universities, uniformity of universities' collectives, isolation of institutions of higher education and their conservatism. Now these factors cease to work that means breaking of the corporate tradition and the actual elimination of Universities corporativism in the long term, which is connected with an introduction of virtual education systems.